Analysis on social change among Bulghar society based on Risalah Ibn Fadlan 922 AD - Halim, Harliana; Yusoff, Kamaruzaman; Ahmad, Shakila; Abdul Khir, Mohd Faizal; Abdullah, Abdul Hafiz; Hamzah, Shahidah; Aziz, Hani Suraya; Saad, Shamsaadal Sholeh; Ebrahimi, Mansoureh (Science Publishing Corporation, 2018)
The role of Islam in the forming of the society solidarity consisting of multi-ethnic backgrounds into a consistency ethno system is a great thing about the Volga Bulgaria that occupied by Bulghar society. The process of Islamization has become the main factors for social changes happened in the society. Thus, this writing is intended to analyse the social changes that occurred in the society that affected Bulghar society achievement, by referred to text analysis on Risalah Ibn Fadlan, 922 AD and some other sources related. For this study, the qualitative method using historical descriptive approach has been employed which involving compilation and evaluation of the facts of the Risalah Ibn Fadlān. Therefore, data onto this study were obtained through library research. The analyses on data study were conducted through texts and document analyses, as well as comparison method. This study finds islamization is the major factor contributing to the social change among Bulghar society. The social change in Bulghar society incorporating the changing of thinking to achieve development in education, the way of life, infrastructure, literature and the spirit of dacwah, the norms and values based on Islam, which the society adheres after becoming Muslim.